2020
DOI: 10.1186/s12886-020-01655-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound cycloplasty and transscleral cyclophotocoagulation for refractory glaucoma in Chinese population

Abstract: Background To compare the efficacy and safety of focused ultrasound cycloplasty (UCP) and transscleral cyclophotocoagulation (TSCP) in the treatment of refractory glaucoma in a Chinese population. Methods We retrospectively compared twenty-eight eligible patients with refractory glaucoma, who were divided into the UCP group and TSCP group. Patients in these two groups underwent a corresponding procedure from June 2018 to February 2019. The intraocular pressure (IOP), visual acuity, the number of anti-glaucom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Reduction of aqueous humour secretion is the leading cause of decreased IOP. Several studies described a significant decrease in IOP from 1 day to 6 months after UCP [ 8 , 10 15 ]. Some studies found that IOP decreased during the 12 months after UCP [ 16 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reduction of aqueous humour secretion is the leading cause of decreased IOP. Several studies described a significant decrease in IOP from 1 day to 6 months after UCP [ 8 , 10 15 ]. Some studies found that IOP decreased during the 12 months after UCP [ 16 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found a 42%-92% success rate at 12 months postprocedure [ 8 ]. Figus et al and Wang et al described a more than 70% success rate at 24 months after UCP [ 10 , 21 ]. Leshno et al found an 87% success rate at 24 months after UCP [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations